PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIIF SMPN 10 TAPUNG - Mutia Suhadah; Rini Dian Anggraini; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was motivated by the percentage of students who reached the KKM was 31%, namely 9 people out of 29 students, it was seen that 69% of students in Class VIIF of SMP 10 Tapung were under the KKM. The KKM set by the school for comparison material is 70. Based on these data, it can be said that the learning outcomes of Class VIIF students in Tapung 10 Middle School on the comparison material are still low. This study aims to improve the learning process and improve the mathematics learning outcomes of Grade VIIF students of 10 Tapung Junior High School in school year 2018/2019 through the application of the STAD type cooperative learning model. The research subjects were VIIF students of 10 Tapung Junior High School in the 2018/2019 academic year totaling 21 people. Data collection instruments in this study are syllabus, lesson plans, student worksheets, and teacher and student activity observation sheets, as well as daily test questions. The results of this study indicate that the average student learning outcomes increased from the basic score of 41.8 to the first cycle to 70.1 with an increase in percentage of 20.85%, then at the base level 41.8 to the second cycle 83.00 with an increase of 29.35%. While the average activity of teachers in the first cycle was 77.78 (moderate) and increased in the second cycle to 96.97 (Very Good) or increased by 37.5. Besides the activity of students with an average in the first cycle is 71.8 (Moderate) and increases in the second cycle to 97.4 (Very Good) or an increase of 35.42. Based on these results it can be concluded that the mathematics learning outcomes of students have increased. Teacher activities and student activities at each meeting also increased. This proves that the application of the STAD type cooperative learning model can improve students' mathematics learning outcomes in class VIIF of Tapung 10 Junior High School.Key Words: Students Math Achievement, Cooperative Learning Model Type STAD